Religion as an Instrument Of Peace - Ineke Tombeng; Deny Adri Tarumingi (International Journal of Integrated Science and Technology, 2024)
This paper focuses on the discourse on religion as an instrument of peace. The basic idea behind this is the emergence of various discriminatory and violent treatments in the name of religion. This reality contradicts the essence and purpose of religion as a source of inspiration, spiritual, ethical, and moral foundation for the formation of a peaceful global community. After exploring the various views on religion, violence and peace itself, my opinion is that in an effort to become an instrument of peace, religions must abandon their dogmatism and institutional arrogance and even their superiority over other religions. Redefining the essence and purpose of religion, mutual acceptance and recognition of existence are the best paths to authentic peace in Indonesian.